(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2016)
Introduction: Effective nursing care by well-trained hands and affectionate heart constitute the backbone of medical intervention in HIV/AIDS. The apprehension often articulated by health professionals while dealing with people living with HIV/AIDS hampers in health care. The purpose of the present study was to assess the extent of knowledge and attitude towards HIV/AIDS amongst nursing students. Methodology: The present cross-sectional study was conducted among 113 selected proficiency certificate level nursing students of Parsa district of Nepal. Pre-tested anonymous questionnaire was administered to collect the responses necessary to infer the extent of knowledge on HIV/AIDS and nature of attitude towards PLWHA. The extent of knowledge was measured through an overall knowledge index constructed based on the responses to 10 objective questions. To ascertain the respondent’s overall attitude, responses to various opinions were scored and summed upto form an attitude index. Results: Almost half of the nursing students had good knowledge while almost a quintile numbers had incomplete knowledge about HIV/AIDS. Majority of them had negative attitude towards the care of PLWHA. Conclusions: In aggregate, nearly half of the respondents had good knowledge about the various aspects of HIV/AIDS; however, majority of them had negative attitude towards the care of PLWHA. The overall knowledge and attitude of senior class was better than their junior counterparts. The training programmes for nurses should aim at confidence and skill building to deal with HIV issues. SAARC J TUBER LUNG DIS HIV/AIDS, 2015; 12(1), Page: 8-13